2009
DOI: 10.3945/ajcn.2008.26834
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phospholipid fatty acid profiles and their association with food intakes: results from a cross-sectional study within the European Prospective Investigation into Cancer and Nutrition

Abstract: These findings indicate that specific plasma phospholipid fatty acids are suitable biomarkers of some food intakes in the EPIC Study. Moreover, these findings suggest complex interactions between alcohol intake and fatty acid metabolism, which warrants further attention in epidemiologic studies relating dietary fatty acids to alcohol-related cancers and other chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
166
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(187 citation statements)
references
References 38 publications
14
166
7
Order By: Relevance
“…Evidence in earlier studies also suggests an inverse association of pentadecanoic acid 15:0 and margaric acid 17:0 with the risk of type 2 diabetes [15,28,32]. Odd chain fatty acids are found in milk fat and fish [33][34][35][36]. There was positive correlation between odd chain fatty acids with DHA (22:6n-3) in this study.…”
Section: Discussionsupporting
confidence: 65%
“…Evidence in earlier studies also suggests an inverse association of pentadecanoic acid 15:0 and margaric acid 17:0 with the risk of type 2 diabetes [15,28,32]. Odd chain fatty acids are found in milk fat and fish [33][34][35][36]. There was positive correlation between odd chain fatty acids with DHA (22:6n-3) in this study.…”
Section: Discussionsupporting
confidence: 65%
“…20 A previous study showed a positive correlation between cellular EPA and DHA with age, and a negative correlation with body mass index. 21 Levels may also differ with ethnicity, even among Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many processed foods, including foods from major companies, still contain high levels of industrially produced trans-fatty acids, despite efforts to reduce them (Aro et al, 1998;McCarthy et al, 2008). A cross-sectional study on plasma fatty acid levels among a sub-sample of our study population (N ¼ 3003) shows a high correlation (r ¼ 0.72, Po0.01) between margarines and elaidic acid (trans 18:1 n-9), a specific biomarker of hardened fats and their related industrial foodstuffs (Saadatian-Elahi et al, 2009). Higher levels of plasma elaidic acid were observed in northern and central than in southern regions, which is compatible with the geographical differences in the consumption of highly processed foods reported in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Details on the rationale, structure and validity of EPIC-SOFT for between-population comparisons are reported elsewhere (Slimani et al, 2002bAl-Delaimy et al, 2005;Ferrari et al, 2009;Saadatian-Elahi et al, 2009).…”
Section: Dietary Variablesmentioning
confidence: 99%